Multistage Long-Term Expansion Planning of Electrical Distribution Systems Considering Multiple Alternatives - Tabares, Alejandra [UNESP]; Franco, John F. [UNESP]; Lavorato, Marina [UNESP]; Rider, Marcos J. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper presents a new mixed-integer linear programming (MILP) model to solve the multistage long-term expansion planning problem of electrical distribution systems (EDSs) considering the following alternatives: increasing the capacity of existing substations, constructing new substations, allocating capacitor banks and/or voltage regulators, constructing and/or reinforcing circuits, and modifying, if necessary, the system's topology. The aim is to minimize the investment and operation costs of the EDS over an established planning horizon. The proposed model uses a linearization technique and an approximation for transforming the original problem into an MILP model. The MILP model guarantees convergence to optimality by using existing classical optimization tools. In order to verify the efficiency of the proposed methodology, a 24-node test system was employed.
Keywords: Distribution system expansion planning; mixed-integer linear programming; multistage long-term planning